Production and characterization of elastomeric cardiac tissue-like patches for Myocardial Tissue Engineering. (October 2020) - Cesur, Sumeyye; Ulag, Songul; Ozak, Lara; Gumussoy, Aleyna; Arslan, Sema; Yilmaz, Betul Karademir; Ekren, Nazmi; Agirbasli, Mehmet; kalaskar, Deepak M.; Gunduz, Oguzhan
Abstract: Cardiovascular disease remains the leading cause of death. Damaged heart muscle is the etiology of heart failure. Heart failure is the most frequent cause of hospital and emergency room admissions. As a differentiated organ, current therapeutics and techniques can not repair or replace the damaged myocardial tissue. Myocardial tissue engineering is one of the promising treatment modalities for repairing damaged heart tissue in patients with heart failure. In this work, random Polylactic acid (PLA), Polylactic acid/Polyethylene glycol (PLA/PEG) and random and aligned Polylactic acid/Polyethylene glycol/Collagen (PLA/PEG/COL) nanofiber patches were successfully produced by the electrospinning technique. In vitro cytotoxic test (MTT), morphological (SEM), molecular interactions between the components (FT-IR), thermal analysis (DSC), tensile strength and physical analysis were carried out after production. The resulting nanofiber patches exhibited beadless and smooth structures. When the fiber diameters were examined, it was observed that the collagen doped random nanofiber patches had the lowest fiber diameter value (755 nm). Mechanical characterization results showed that aligned nanofiber patches had maximum tensile strength (5.90 MPa) values compared to PLA, PLA/PEG, and PLA/PEG/COL (random). In vitro degradation test reported that aligned patch had the highest degradation ratio. The produced patches displayed good alignment with tissue on cardiomyocyte cell morphology studies. In conclusion, newly produced patches have noticeable potential as a tissue-like cardiac patch for regeneration efforts after myocardial infarction. Highlights: The PLA/PEG/Collagen nanofiber patches were produced successfully by using electrospinning method. The high speed of the collector affected the nanofiber orientation by changing from random to aligned structures. The high amount of PEG had a toxic effect on the cardiomyocyte cell line (H9C2). Aligned nanofiber patches showed superior tensile strength value compared to the random nanofiber. The effect of aligned structure on cardiomyocyte cell behavior observed efficiently.